First Comparative Transcriptomic Analysis of Wild Adult Male and Female Lutzomyia longipalpis, Vector of Visceral Leishmaniasis - Mccarthy, Cristina Beryl (2013)
Leishmaniasis is a vector-borne disease with a complex epidemiology and ecology. Visceral leishmaniasis (VL) is its most severe clinical form as it results in death if not treated. In Latin America VL is caused by the protist parasite Leishmania infantum (syn. chagasi) and transmitted by Lutzomyia longipalpis. This phlebotomine sand fly is only found in the New World, from Mexico to Argentina. However, due to deforestation, migration and urbanisation, among others, VL in Latin America is undergoing an evident geographic expansion as well as dramatic changes in its transmission patterns. In this context, the first VL outbreak was recently reported in Argentina, which has already caused 7 deaths and 83 reported cases. Insect vector transcriptomic analyses enable the identification of molecules involved in the insect?s biology and vector-parasite interaction. Previous studies on laboratory reared Lu. longipalpis have provided a descriptive repertoire of gene expression in the whole insect, midgut, salivary gland and male reproductive organs. Nevertheless, the study of wild specimens would contribute a unique insight into the development of novel bioinsecticides. Given the recent VL outbreak in Argentina and the compelling need to develop appropriate control strategies, this study focused on wild male and female Lu. longipalpis from an Argentine endemic (Posadas, Misiones) and a Brazilian non-endemic (Lapinha Cave, Minas Gerais) VL location. In this study, total RNA was extracted from the sand flies, submitted to sequence independent amplification and high-throughput pyrosequencing. This is the first time an unbiased and comprehensive transcriptomic approach has been used to analyse an infectious disease vector in its natural environment. Transcripts identified in the sand flies showed characteristic profiles which correlated with the environment of origin and with taxa previously identified in these same specimens. Among these, various genes represented putative targets for vector control via RNA interference (RNAi).